Status of registration, re-registration, and accreditation of ethics committees with Central Drugs Standard Control Organization, Department of Health Research, and National Accreditation Board for Hospitals and Healthcare Providers – An evaluation of the extent of ethics oversight in the country - Ananya Rakshit; Karan Muzumdar; Nithya Jaideep Gogtay; Yashodhan Desai; Urmila Mukund Thatte (Perspectives in Clinical Research)
Context: The “New Drugs and Clinical Trials Rules 2019” mandates that Ethics Committees (ECs) register with the Central Drugs Standard Control Organization (CDSCO), while ECs overseeing Postgraduate (PG) theses and academic studies must register with the Department of Health Research (DHR). National Accreditation Board for Hospitals and Healthcare Providers (NABH) accreditation of ECs is currently optional. Aim: To evaluate the current status of EC registration and re-registration with CDSCO, DHR and accreditation of NABH as a metric of ethical oversight. Subjects and Methods: Data from January 1, 2019, to September 30, 2022 were collected from the organizational websites and the National Medical Commission (NMC). Registration and re-registration data for ECs were matched against the volume of studies in the Clinical Trials Registry India (CTRI), the number of ECs per state, and state populations. Descriptive and inferential statistics were applied. Results: Of the 770 ECs registered with CDSCO, 38.3% were reregistered. Of the 977 DHR-registered ECs, only 17% were re-registered. Among 370 NMC-recognized PG medical institutes, 49.72% had DHR-registered ECs. Only 13% (186/1400) ECs were NABH accredited from the overall data. A total of 14,551 regulatory studies were registered with CTRI. Among the major states (>4% of Indian population), Maharashtra had the highest percentage of CDSCO-registered ECs at 20% and accounted for 14% of regulatory studies, while states such as Bihar and West Bengal had lower percentages of both CDSCO registered ECs and regulatory studies. Conclusion: The registration, re-registration status of ECs, and accreditation are not commensurate with the quantum of regulatory and academic studies in the country.